Advanced Methods in the Mathematical Modeling of Economics, Econometrics, and Financial Management (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Special Issue delves into the crucial role of mathematical modeling in modern economics. It explores how advanced methodologies in econometrics and financial management serve as powerful tools for understanding and navigating the complexities of economic change. By applying precise quantitative methods, contributors to this Special Issue demonstrate how to derive optimal solutions, achieve competitive advantages for businesses and nations, and improve forecasting accuracy beyond vague assumptions. The collection highlights the importance of comprehensive financial perspectives in accelerating effective decision-making, reducing information asymmetry, and securing essential resources for innovation and growth. It specifically addresses contemporary challenges such as business model transformation and the optimization of corporate finance, offering insights into adapting to new industries, products, and global market dynamics while ensuring profitability. This Special Issue is an invaluable resource for researchers and practitioners interested in the cutting-edge intersection of mathematics, economics, and finance.